Domestic Security in the Maghreb: Deficits and Counter-Measures - Hanspeter Mattes (German Institute of Global and Area Studies (GIGA), 2012)
Terrorism and crime, particularly organised crime with its close links to terrorism, currently constitute the greatest challenges to the domestic security of the Maghreb states Algeria, Libya, Morocco and Mauretania. Additional challenges have resulted from the social protests of 2011 in Tunisia, Egypt and Libya, which gained unexpected political momentum and culminated in the ousting of regimes. Terrorism and organised crime are, to varying extents, prevalent in all Maghreb states and have led to the introduction of extensive counter-measures by governments and security agencies. These measures comprise five categories of activity: (1) increased personnel for security agencies and efficiency-enhancing reforms within these agencies; (2) a significant increase in and upgrading of equipment for security agencies; (3) the strengthening of the legal foundation (laws, regulations) for combating these offences with judicial measures; (4) an increase in bilateral, regional and international cooperation in the field of security; and (5) the implementation of preventive measures. The fifth measure, however, has received considerably less attention than the others. Some measures have entailed human rights violations. Nonetheless, as yet their use has sufficed to contain the threats posed by terrorism and crime.
Keywords: 300; terrorism; crime; North Africa; security governance; Politische Gewalt; Kriminalität; Nationale Sicherheit; Governance-Ansatz; Maghreb-Staaten